Perlindungan Hak Konstitusional Di Indonesia - Herdi Munte; Christo Sumurung Tua Sagala (Jurnal Ilmiah Penegakan Hukum, 2021)
The basis for the establishment of the Constitutional Court is an effort to uphold the principles of a rule of law and to provide maximum protection for democracy and basic rights of citizens. As the main objective of the rule of law is to protect the freedom of individual citizens from the State's power. The purpose of this research is to answer the question of what constitutional rights are citizens and how they are protected in Indonesia. This research uses a normative juridical approach by examining theories, concepts, legal principles and laws and regulations obtained from legal material sources such as books, articles / writings and other documents, then the data is analyzed so that it will provide conclusions. The results show that constitutional rights are rights that include civil rights, political rights, economic rights, and socio-cultural rights guaranteed by the 1945 Constitution, for their protection efforts through the process of forming laws that reflect the protection and respect for human rights and dignity. and dignity and if there is a law that is detrimental to their rights, they can file a constitutionality review in the Constitutional Court